Is a High Tone Pointy? Speakers of Different Languages Match Mandarin Chinese Tones to Visual Shapes Differently - Shang, Nan; Styles, Suzy J. (Frontiers in Psychology, 2017)
Studies investigating cross-modal correspondences between auditory pitch and visual shapes have shown children and adults consistently match high pitch to pointy shapes and low pitch to curvy shapes, yet no studies have investigated linguistic-uses of pitch. In the present study, we used a bouba/kiki style task to investigate the sound/shape mappings for Tones of Mandarin Chinese, for three groups of participants with different language backgrounds. We recorded the vowels [i] and [u] articulated in each of the four tones of Mandarin Chinese. In Study 1 a single auditory stimulus was presented with two images (one curvy, one spiky). In Study 2 a single image was presented with two auditory stimuli differing only in tone. Participants were asked to select the best match in an online ‘Quiz’. Across both studies, we replicated the previously observed ‘u-curvy, i-pointy’ sound/shape cross-modal correspondence in all groups. However, Tones were mapped differently by people with different language backgrounds: speakers of Mandarin Chinese classified as Chinese-dominant systematically matched Tone 1 (high, steady) to the curvy shape and Tone 4 (falling) to the pointy shape, while English speakers with no knowledge of Chinese preferred to match Tone 1 (high, steady) to the pointy shape and Tone 3 (low, dipping) to the curvy shape. These effects were observed most clearly in Study 2 where tone-pairs were contrasted explicitly. These findings are in line with the dominant patterns of linguistic pitch perception for speakers of these languages (pitch-change, and pitch height, respectively). Chinese English balanced bilinguals showed a bivalent pattern, swapping between the Chinese pitch-change pattern and the English pitch-height pattern depending on the task. These findings show for that the supposedly universal pattern of mapping linguistic sounds to shape is modulated by the sensory properties of a speaker’s language system, and that people with high functioning in more than one language can dynamically shift between patterns.